A bastard kind of reasoning : William Blake and geometry - Cooper, Andrew M., 1953- (State University of New York Press, 2023)
What do Einsteinian relativity, eighteenth-century field theory, Neoplatonism, and the overthrow of three-dimensional perspective have in common? The poet and artist William Blake's geometry--the conception of space-time that informs his work across media and genres. In this illuminating, inventive new study, Andrew M. Cooper reveals Blake to be the vehicle of a single imaginative vision in which art, literature, physics, and metaphysics stand united. Romantic-period physics was not, as others have assumed, materialist. Blake's cosmology forms part of his age's deep reevaluation of body and soul, of matter and Heaven, and even probes what it is to understand understanding, reason, and substance. Far from being anti-Newtonian, Black was prophetically post-Newtonian. His poetry and art realized the revolutionary potential of Enlightened natural philosophy even as that philosophy still needed an Einstein for its physics to snap fully into focus. Blake's mythmaking exploits the imaginative reach of formal abstractions to generate a model of how sensation imparts physical extension to the world. More striking still, Cooper shows how Blake's art of vision leads us today to visualize four-dimensional concepts of space, time, and Man for ourselves--back cover.
Description based upon print version of record.
Keywords: Blake, William, -- 1757-1827 -- Criticism and interpretation.; Newton, Isaac, -- 1642-1727 -- Influence.; Blake, William, -- 1757-1827; Newton, Isaac, -- 1642-1727; Literature and science -- Great Britain -- History -- 18th century.; Geometry in literature.; Mathematics in literature.; Physics in literature.; Space and time in literature.; Littérature et sciences -- Grande-Bretagne -- Histoire -- 18e siècle.; Géométrie dans la littérature.; Mathématiques dans la littérature.; Physique dans la littérature.; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh.; Geometry in literature; Influence (Literary, artistic, etc.); Literature and science; Mathematics in literature; Physics in literature; Space and time in literature; Great Britain; 1700-1799; Criticism, interpretation, etc.; History